1996
DOI: 10.1128/jb.178.12.3608-3613.1996
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the DnaK-DnaJ-GrpE chaperone team in protein secretion in Escherichia coli

Abstract: We used depletion studies designed to further investigate the role of the DnaK, DnaJ, and GrpE heat shock proteins in the SecB-dependent and SecB-independent secretion pathways. Our previous finding that SecBdeficient strains containing the grpE280 mutation were still secretion proficient raised the possibility that GrpE was not involved in this secretory pathway. Using depletion studies, we now demonstrate a requirement for GrpE in this pathway. In addition, depletion studies demonstrate that while DnaK, DnaJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 47 publications
3
81
0
Order By: Relevance
“…3, lane 6). This result is consistent with the observation that DnaK depletion exacerbates OmpA export defects produced by the disruption of secB (4,5). More significantly, overexpression of dnaK E171K did not block OmpA export in tigϪ/secBϪ cells (Fig.…”
Section: Fig 2 Disruption Of Tig Enhances Bla Export In Srp-deficiesupporting
confidence: 81%
See 2 more Smart Citations
“…3, lane 6). This result is consistent with the observation that DnaK depletion exacerbates OmpA export defects produced by the disruption of secB (4,5). More significantly, overexpression of dnaK E171K did not block OmpA export in tigϪ/secBϪ cells (Fig.…”
Section: Fig 2 Disruption Of Tig Enhances Bla Export In Srp-deficiesupporting
confidence: 81%
“…Although the Bla targeting pathway(s) has never been clearly identified, previous studies have shown that a variety of physiological insults that increase the presence of abnormal proteins (and that likely induce the heat shock response) lead to Bla export defects (7,34). These and other results (5) suggest that Bla is targeted by one or more heat shock-regulated chaperones such as DnaK or GroEL. Inactivation of the SRP pathway has often been observed to delay Bla export, but as previously proposed (35) this effect is probably an indirect consequence of perturbing the function of heat shock proteins.…”
Section: Disruption Of Tig Reduces the Requirement For Targeting Factmentioning
confidence: 78%
See 1 more Smart Citation
“…Specifically, it has been reported that DnaK can substitute in the export of several SecB-dependent secretory proteins (35) and that the DnaK and GroEL chaperone machines can assist protein export in some other cases as well (36,37). Furthermore, similar to the DnaK system, SecB can prevent luciferase from aggregation and cooperate with DnaK͞DnaJ͞GrpE in the refolding of luciferase in vitro (13).…”
Section: Discussionmentioning
confidence: 99%
“…SecB is a tetramer that interacts with its ligands via an ATP-independent kinetic partitioning mechanism (5,6). Several studies have indicated that highly abundant molecular chaperones such as DnaK and GroEL, which play essential roles in protein folding, can also maintain the transport competence of presecretory proteins (7)(8)(9)(10). DnaK and GroEL are structurally unrelated to SecB and bind polypeptides in an ATP-dependent cycle that is regulated by co-chaperones (11,12).…”
mentioning
confidence: 99%